MULTI-COMPONENT WAVEFIELD SEPARATION APPLIED TO HIGH-RESOLUTION SURFACE SEISMIC DATA - Richwalski S.; Roy-Chowdhury K.; Mondt J.C. (My University, 2001)
A detailed characterisation of the subsurface using high-resolution multi-component seismic data requires additional processing. We adapted a frequency-domain wavefield separation method and applied it in an iterative way to subsets of a nine-component CMP survey recorded in The Netherlands. The method is well suited to remove the Rayleigh-wave. Further decomposition of the data in the case of two-component wavefield separation made it possible to group P- and S-wave sections and attempt an interpretation of events based on zero-offset arrival times, computed from existing velocity-depth profiles. Three-component separation failed beyond the extraction of the Rayleigh wave because events were not sufficiently present on all receiver components to allow for a description in terms of all polarisation parameters. The absence of the Love wave due to subsurface conditions simplified the processing of the data subset, with source and receivers oriented in a crossline-horizontal direction, to a depth converted stack, which agrees with results found earlier. The detected dipping of a peat layer was later confirmed by cone penetration tests (CPT).
Keywords: SHALLOW SEISMIC; MULTICOMPONENT; HIGH-RESOLUTION; SEPARATION; WAVEFIELD DECOMPOSITION